99 lat działalności Ligi Morskiej i Rzecznej na rzecz krzewienia idei „Polski morskiej” - Kozłowska, Aneta (Biuletyn Historii Wychowania, 2017)
This article presents the history of the Liga Morska i Rzeczna during its 99 years of activties promoting the idea of a marine Poland. The task of this organization is the broadly understood concept of development which is to be achieved by development of the principles of the organization of ports, shipping, universal maritime terminology, the development of shipping, the construction of the waterway system in Poland, the training of personnel and the promotion of shipping and maritime sports in Polish society. In addition, the text describes the various types of activities of Liga Morska i Rzeczna, such as launching publications related to maritime issues, creating plans for the construction of the port of Gdynia, the Naval Yard and the expansion of the city of Gdynia, collecting money for ship construction and promotional activities. The article also includes the relationship between the actions of Liga Morska i Rzeczna and the expansion of the Polish Navy. The conclusion mentions an exhibition organized by the Library of the Polish Naval Academy in Gdynia which will travel throughout Poland over the next two years.